PENGARUH KOMITMEN PROFESIONAL DAN KOMITMEN ORGANISASI TERHADAP KINERJA INTERNAL AUDITOR DENGAN ETIKA KERJA ISLAM SEBAGAI VARIABEL INTERVENING (Studi Empiris Pada Internal Auditor Bank Muamalat Indonesia Wilayah Jawa Tengah) - Gunawan Aji (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2013)
A lot of studies about professional commitment and organization commitment have been done, but study to test how work of professional commitment and commitment organization effects the objective professional commitment and organization commitment was rare. The objective of this research is to examine the influence of professional commitment and commitment organization to job performance and islamic work ethic as intervening variable. The primary data used was from internal auditor perception of all internal auditor of PT. Bank Muamalat Indonesia, one of shariah banking in Indonesia. The questionnaires were distributed to 150 internal auditor as respondents and 40 of questionnaires were returned and can be used. The path analysis model used to test the hypothesis of this research. The research finding figures that not of all hypothesis mentioned and built earlier could be accepted. From 7 (seven) hypothesis, there were only 4 (four) hypothesis admitted or accepted. The result supported H2, H5, H6 and H7, these indicated that professionalism has positively influence islamic work ethic and islamic work ethic has positively influence job performance. The commitment organization has not influence islamic work ethic and job performance.